Correction: A robust iron catalyst for the selective hydrogenation of substituted (iso)quinolones. Issue 40 (28th September 2018) - Sahoo, Basudev; Kreyenschulte, Carsten; Agostini, Giovanni; Lund, Henrik; Bachmann, Stephan; Scalone, Michelangelo; Junge, Kathrin; Beller, Matthias
Abstract : Correction for 'A robust iron catalyst for the selective hydrogenation of substituted (iso)quinolones' by Basudev Sahoo et al., Chem. Sci., 2018, DOI: ;10.1039/c8sc02744g .